Two‐Photon Printing of Shape‐Memory Microstructures and Metasurfaces via Radical‐Mediated Thiol‐Vinyl Hydrothiolation. Issue 9 (30th March 2022) - Jeske, Madelyn P.; Zhang, Wenshi; Anthamatten, Mitchell
Abstract: Shape‐memory resists capable of high‐resolution curing into arbitrarily designed structures are increasingly demanded for soft robotics, optical sensors, microscale manufacturing, and biomedicine. Amorphous, shape‐memory thiol‐vinyl networks are printed using two‐photon polymerization (2PP) curing of a simple resin formulated with commercially available reagents. The ability to print high‐resolution feature sizes down to 200 nm is attributed to the use of radical‐mediated, thiol‐vinyl step‐growth polymerization that quickly cross‐links the resin, limiting diffusive transport. The thermomechanical behavior of the 2PP‐cured material analyzed in compression, tension, and three‐point bending is similar to the behavior of the UV‐polymerized samples. To demonstrate the ability to design, field, and test 4D responsive microstructures, an array of nine springs with coil diameters of 330 µm is printed. Following compressive shape‐fixing, printed arrays can release 11 µJ of stored elastic strain energy when reheated. Further, a new concept of dichroic‐memory of a metamaterial device is demonstrated by printing a twisted woodpile structure with circular dichroism as characterized by Mueller Matrix ellipsometry. The results of this study demonstrate how combining high‐resolution 2PP curing with stimuli‐responsive molecular architectures can further the engineering of responsive microstructures and metamaterials. Abstract : A multifunctional thiol‐vinyl resin is two‐photon polymerized to create high‐resolution, shape‐memory microstructures with feature sizes beneath 200 nm. Shape‐memory of printed spring‐arrays is evaluated under compression, confirming the ability to design, field, and test 4D responsive microstructures. A twisted woodpile structure is printed that demonstrates how dichoric‐memory can emerge from a metamaterial's underlying shape‐memory.